POST-PANDEMIC SELF-REGULATED LEARNING AMONG JUNIOR HIGH STUDENTS: A QUASI-EXPERIMENTAL STUDY - Nurin Baroroh; Nur Hafifah (Jurnal At-Taujih, 2026)
The COVID-19 pandemic has diminished students' self-regulated learning (SRL) abilities, as evidenced by procrastination and a culture of instant gratification in the digital age. This study aims to examine the effectiveness of time management and goal-setting training in improving SRL post-pandemic. A quasi-experimental method with a one-group pretest-posttest design was used, involving eight eighth-grade students from Class VIII A at MTs X Banyuwangi who exhibited low SRL. Analysis using the Wilcoxon test showed an increase in scores with a p-value of 0.012 (p < 0.05), indicating a significant change in students' SRL after the training, with an average increase of 4.50. Qualitative findings support these results, showing increased metacognitive awareness, the ability to prioritize tasks, and a reduction in digital distractions. This study confirms that time management and goal-setting training is effective as an initial strategy for building students' learning autonomy during the post-pandemic transition period.